Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2017 - Ao, Sio-Iong; Kim, Haeng Kon; Castillo, Oscar; Chan, Alan Hoi-Shou; Katagiri, Hideki (Springer Nature Singapore : Imprint: Springer, 2018)
This volume contains a selection of revised and extended research articles written by prominent researchers participating in the 25th International MultiConference of Engineers and Computer Scientists (IMECS 2017) which was held in Hong Kong, 15-17 March, 2017. Topics covered include electrical engineering, communications systems, engineering mathematics, engineering physics, and industrial applications. With contributions carefully chosen to represent the most cutting-edge research presented during the conference, the book offers the state of art in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.